2011
DOI: 10.7763/ijcte.2011.v3.320
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of High Speed II Rand FIR Filter using Pipelining

Abstract: The FIR & IIR Filters are being designed using HDL languages since speed is among the chief interest in this era; the main objective is to enhance the speed of the system. In the whole system if the speed of the individual block is enhanced the overall speed of the system is enhanced digital computer arithmetic is an aspect of logic design with the objective of developing appropriate algorithms in order to attain an effective utilization of the available hardware. Since ultimately, speed, power and chip area a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Where x(n) is the input signal, y(n) is the output signal, bi is the filter coefficients and N is the filter order [5].…”
Section: Fir Filtermentioning
confidence: 99%
“…Where x(n) is the input signal, y(n) is the output signal, bi is the filter coefficients and N is the filter order [5].…”
Section: Fir Filtermentioning
confidence: 99%
“…Many studies are presented an optimisations design approach such as dispersed look ahead [13,14], clustered look ahead [14,15] and distributed look ahead [16,17]. All these methods increased the operating frequency using superfluous poles allowing pipelining [18,19]. Though, towards limitation on scale factors and noise effect, these design approaches need intensive computational time the adequate set for zeros and poles and proper order for the sub-filters.…”
Section: Introductionmentioning
confidence: 99%
“…This computation work is required in advance to realise the actual filter. On the other hand, some research works based on optimal design is offered to minimize the consumed computational time, however, the attempt still limited [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of FIR and IIR filters on FPGA is carried out in [44] and results showed that pipelined filters shows advantages over non pipelined filters in terms of speed and area on FPGA.…”
Section: Literature Reviewmentioning
confidence: 99%